Effect of heat treatment temperature to the crystal growth and optical performance of Mn3O4 doped α-Zn2SiO4 based glass-ceramics - Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Abd. Aziz, Sidek; Mohamed Kamari, Halimah; Yap, Wing Fen; Yaakob, Yazid; Sa'at, Nor Kamilah; Gyrol, Ali; Şakar, Erdem (Elsevier, 2019)
In this work, manganese (II, III) oxide, (Mn3O4) doped zinc soda lime silica glasses have been synthesized using a conventional melt-quenching process and followed by control heat treatment process. The crystal phase composition and optical properties of α-Zn2SiO4:Mn3O4 based glass-ceramics are comprehensively studied. The physical properties and crystal growth of α-Zn2SiO4 phase were measured by density analysis, linear shrinkage, X-ray diffraction (XRD) and Fourier transform infrared reflection (FTIR) spectroscopy. From the measurement, the average density and linear shrinkage of α-Zn2SiO4:Mn3O4 based glass-ceramics increased with increasing heat treatment temperature. Besides, the presence of Zn–O–Si bands indicates the formation of α-Zn2SiO4 crystal phase and causing the decrement of energy band gap. The photoluminescence spectra of Mn2+ ions exhibit emission transitions of 4T1(G)–6A1(S) and show a prominent green emission colors of α-Zn2SiO4 phase at 524 nm.